The Effect of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on Dividend Payout Ratio (DPR) at PT Akasha Wira Internasional Tbk. for the Years 2011-2020 - Poni Yanita; Tiara Lilis surya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to determine: 1.) Effect of Return On Assets (ROA) Current Ratio (CR) and Debt To Equity Ratio (DER) on Dividend Payout Ratio (DPR) at PT Akasha Wira Internasional Tbk. 2011-2020 Partially or Simultaneously, 2.) What is the Effect of Return On Assets (ROA) Current Ratio (CR) and Debt To Equity Ratio (DER) at PT Akasha Wira Internasional 2011-2020. In this study, researchers used quantitative research methods.The type of data used is secondary data. Data collection techniques thatused in this study using library research. With data analysis technique that uses multiple linear regression analysis and testhypothesis by using SPSS Version 26 . Based on the results of the study, it shows that: ROA has a significant effect on the Dividend Payout Ratio (DPR) at PT Akasha Wira Internasional Tbk in 2011-2020, CR has an effect on the Dividend Payout Ratio (DPR) in PT Akasha Wira Internasional Tbk in 2011- 2020. However, DER Does not affect the Dividend Payout Ratio (DPR) at the company PT Akasha Wira Internasional Tbk. Simultaneously there is a significant effect on ROA, CR, and DER at the DPR PT Akasha Wira Internasional Tbk 2011-2020. The regression equation obtained is: Y=-0,328+0.868X1+0.321X2-1,056X3. The effect of ROA, CR and DER on DPR at PT Akasha Wira Internasional Tbk 2011-2020 is only 21% while the remaining 79% is influenced by other factors not examined in this study.